2012
DOI: 10.1103/physrevb.85.104109
|View full text |Cite
|
Sign up to set email alerts
|

First-principles prediction of oxygen octahedral rotations in perovskite-structure EuTiO3

Abstract: We present a systematic first-principles study of the structural and vibrational properties of perovskite-structure EuTiO 3 . Our calculated phonon spectrum of the high-symmetry cubic structural prototype shows strong M-and R-point instabilities, indicating a tendency to symmetry-lowering structural deformations composed of rotations and tilts of the oxygen octahedra. Subsequent explicit study of 14 different octahedral tilt-patterns showed that the I 4/mcm, I mma, and R3c structures, all with antiferrodistort… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
63
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(77 citation statements)
references
References 46 publications
14
63
0
Order By: Relevance
“…The presence of FM phase due to the substitution of a nonmagnetic ion may be explained by the super-exchange mechanism. It is reported that in bulk EuTiO 3 AFM phase can originate at T < 5.5 K from direct AFM type exchange interaction between Eu +2 ions and indirect super-exchange Eu 2+ − O 2-− Eu 2+ [12]. Therefore, it may be assumed that a super-exchange between Eu 2+ − Sr +2 − Eu 2+ could be responsible for the ferromagnetic phase .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of FM phase due to the substitution of a nonmagnetic ion may be explained by the super-exchange mechanism. It is reported that in bulk EuTiO 3 AFM phase can originate at T < 5.5 K from direct AFM type exchange interaction between Eu +2 ions and indirect super-exchange Eu 2+ − O 2-− Eu 2+ [12]. Therefore, it may be assumed that a super-exchange between Eu 2+ − Sr +2 − Eu 2+ could be responsible for the ferromagnetic phase .…”
Section: Discussionmentioning
confidence: 99%
“…Bulk quantum paraelectric EuTiO 3 is AFD below about 281 K [9,10,11,12], antiferromagnetic (AFM) at temperatures lower than 5.5 K and paraelectric at all other temperatures [1,2]. Using first principles calculations, Fennie and Rabe [13] predicted the presence of simultaneous ferromagnetic (FM) and ferroelectric (FE) phases in (001) EuTiO 3 thin films under compressive epitaxial strains exceeding 1.2%.…”
Section: Introductionmentioning
confidence: 99%
“…In analogy to STO, ETO also undergoes an antiferrodistortive SPT from P m3m to I4/mcm (a 0 a 0 c − in Glazer notation) driven by R-point phonon softening [7]. While the SPT at 105 K in STO has been extensively studied for decades, the transition in ETO was observed only recently [8] but has since attracted much attention in the field and has been the focus of numerous experimental [7,[9][10][11][12][13][14][15] and theoretical [16][17][18] studies.…”
Section: Introductionmentioning
confidence: 99%
“…Howard and Stokes have taken the 23 tilt systems proposed by Glazer 6 and using group-theory, simplified the list to 15 distinct tilt systems 7 . These group theoretic tools have proven invaluable in analyzing rotational instabilities in a wide range of perovskites [8][9][10][11] . In this work, we investigate the stability of Li 3 OCl using lattice dynamics.…”
Section: Introductionmentioning
confidence: 99%